FILOSOFI PENDIDIKAN DASAR DALAM MENDUKUNG PROSES SOSIALISASI ANAK SEKOLAH DASAR - Haidir, Haidir; Suhendra, Irwan; Desyandri, Desyandri; Jamaris, Jamaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development child's socialization process is needed to adapt according to the stages of development and age of the child. The problem studied in this study is the development of the socialization process identified through the role of teachers in establishing relationships with students in character bulding at school environment. The problem studied in this study is the development of the socialization process identified through the role of teachers in establishing relationships with students in a school environment. The results showed that not all hands appeared in the development stage of the child's socialization process because children just recognized the concept and did not yet arrive at a concrete understanding like adults (socialization stage). Children need to be given direction and guidance to behave according to their stages of development so that they can understand the meaningfulness of life in playing a role and placing themselves in the school environment. Based on the six indicators used for socialization, the stages of self-role, socialization in life, andcognitive development are found. For other steps, it is necessary to provide understanding by teachers in the school environment and families from the environment outside the school.